General physiology of oligodendrocytes - Butt, Arthur M. (Henry Stewart Talks, 2022)
Oligodendrocytes, White matter, Myelin, The myelin sheath, Demyelination, Axons, Oligodendrocyte precursor cells (OPC), Myelin pathology